Leisure Satisfaction, Personality, and Psychosexual Adjustment Among College Students: A Latent Profile Analysis - Xia, Ximei; Wang, Xiaotian; Wang, Yuting (Frontiers in Psychology, 2022)
Although the factors influencing sexual health have been explored by researchers, the impact of leisure and personality on psychosexual adjustment and the interaction of these two factors remain unknown. This study investigated the relationship between leisure satisfaction and psychosexual adjustment based on the compensation theory and the social learning theory. The differences in psychosexual adjustment across different personality types were also explored. Finally, we examined the interaction between personality and leisure satisfaction based on the personal-environment fit models. The participants in this study were 1,161 college students. The results supported all the hypotheses proposed. There was a significant positive correlation between leisure satisfaction and psychosexual adjustment. Participants of four personality types (the overcontrolled, high-moderate, low-moderate, and resilient groups) had different performance in psychosexual adjustment. The resilient group had the highest scores, while the overcontrolled group had the lowest scores. The results suggest that there is an interaction between personality and leisure satisfaction. Our research could enrich the research contents of leisure and personality and provide a practical basis for the improvement of college students in psychosexual adjustment.